The Ineffective Role of Cathodal tDCS in Enhancing the Functional Motor Outcomes in Early Phase of Stroke Rehabilitation: An Experimental Trial. (5th May 2014) - Fusco, Augusto; Assenza, Federica; Iosa, Marco; Izzo, Simona; Altavilla, Riccardo; Paolucci, Stefano; Vernieri, Fabrizio
Abstract : Transcranial direct current stimulation (tDCS) is a noninvasive technique that could improve the rehabilitation outcomes in stroke, eliciting neuroplastic mechanisms. At the same time conflicting results have been reported in subacute phase of stroke, when neuroplasticity is crucial. The aim of this double-blind, randomized, and sham-controlled study was to determine whether a treatment with cathodal tDCS before the rehabilitative training might augment the final outcomes (upper limb function, hand dexterity and manual force, locomotion, and activities of daily living) in respect of a traditional rehabilitation for a sample of patients affected by ischemic stroke in the subacute phase. An experimental group (cathodal tDCS plus rehabilitation) and a control group (sham tDCS plus rehabilitation) were assessed at the beginning of the protocol, after 10 days of stimulation, after 30 days from ending of stimulation, and at the end of inpatient rehabilitation. Both groups showed significant improvements for all the assessed domains during the rehabilitation, except for the manual force, while no significant differences were demonstrated between groups. These results seem to indicate that the cathodal tDCS, provided in an early phase of stroke, does not lead to a functional improvement. To depict a more comprehensive scenario, further studies are needed.